Ut pictura poesis: Visual rhetoric in Homeric controversy of the early 18th century - M. S. Neklyudova (Шаги, 2023)
During 1714–1716, a stormy, if short-lived, polemic broke out in France over Homer and his place in the literary canon. Its participants debated how his works should be assessed and how they should be translated, verbatim or freely. Homer’s opponents, led by Houdar de La Motte, pointed to the immorality of Homeric heroes, their stubbornness and cruelty; they also dwelled on the compositional flaws of his poems, showing their incompatibility with modern aesthetic standards. For their part supporters of the ancient poet, led by Madame Dacier, insisted on the historical and cultural distance which separated the works of Homer from modernity, and argued that they could not be evaluated according to the standards of another era. In this exchange of opinions, both sides used the same topoi and figures of speech because they were engaged in public controversy and therefore competed in rhetoric. The article considers one such topos, which equates Homer with an artist — a sculptor or a painter — and treats his writings as sculptures or paintings. This equation represents an interesting twist on the traditional saying ‘ut pictura poesis’, and is used by both parties, but for different purposes and with varying rhetorical effectiveness.